Transformation of Educational Information Technology: An Analysis of the Development of Islamic Universities in Pakistan - Shakeer, Malik Muzaffar; Husni, Talita Afifah (Institut Agama Islam Negeri Lhokseumawe, 2024)
This research explicitly examines the strategy model employed in the growth of Islamic institutions in terms of educational technology plans geared at organizational sustainability. The research employs a qualitative approach. The study's interpretation is applicable and backed by field data, resulting in a model for the establishment of Islamic institutions that may serve as a reference in Pakistan. This study examines studies on strategic goals, curricular relevance to industry demands, and employment outcomes for university graduates. The survey found no substantial difference between Islamic and regular universities. The university's development strategy is in line with the government. As such, colleges have been given the option to develop creative programs. In this situation, program innovation is driven by technology and information. The Islamic University of Pakistan conducted employment market and labor research, as well as studies that illustrate the pattern of using Information Communication Technology (ICT), which revealed significant developments in the field of sustainability and community oriented. Furthermore, the study's findings revealed a gap between activities at Islamic institutions and the experiences and skills required for young people to enter the information technology business. The paper has consequences for innovation and shifting priorities in higher education policy.